Love attitudes in romantic and marital relationships - Fourmanov, Igor A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The differences in love attitudes depending on the status of partnerships are considered. In the hierarchy of love attitudes of partners in both romantic and marital relationships, Eros, Mania and Agape occupy a dominant position. In partners who are in a romantic relationship, Agape, Ludus and Storge are more pronounced, in partners who are in a marital relationship – Mania. No statistically significant differences were found in Eros and Pragma scores. Men who are in a romantic relationship, have significantly higher rates of attitudes Agape, Storge and Ludus. Men who are in a marital relationship, significantly different higher scores of Eros and Mania. No statistically significant differences were found in the Pragma score. Women who are in a romantic relationship have significantly higher scores of attitudes Storge and Eros, women who are in a marital relationship – Mania. Other attitudes are not significantly different.
Keywords: romantic and marital relationships; love attitudes; Eros; Ludus; Storge; Pragma; Mania; Agape